The concept and types of state control in public services delivery - Salieva Shakhsanem Usnatdinovna (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article analyzes the organizational and legal mechanisms for ensuring legality and discipline in the provision of public services in Uzbekistan. It examines various forms of control (parliamentary, judicial, presidential, governmental, and departmental) and their impact on the quality of public services. Key challenges identified include the absence of comprehensive legislation and the ineffective application of the Law “On Administrative Procedures”. It offers recommendations for improving the regulatory framework and control practices to enhance the transparency and efficiency of the public service system.